Analysis of the environmental effects of gated communities on the neighborhood in the context of environmental stress - Akgün, Asiye Gültekin; Ünlü, Alper (Yıldız Technical Univ, Fac Architecture, Merkez Yerlesim, Besiktas, İstanbul, 34349, Turkey, 2015)
In this study, as part of the phenomenon of urban segregation, gated residential communities are discussed in the context of environmental stress. Gated communities, whose theoretical infrastructure is tried to be understood through political economy readings, are shaped upon two concepts basically; segregation and othering. Gated communities eliminate social connectedness with their physical barriers. The social, economic and symbolic oppositions that push each other in the context of gated community reveal a tension between the residents and non-residents of the gated compound. In order to measure the assumed tension, environmental stress parameters have been used. An interview form has been prepared for the purpose of finding out how the determined stress parameters are perceived by the ones living around the gated community. This interview form has been applied to dwellers around gated compounds which are located in three different areas with different urban syntactic values and different socio-economic structures. The statistical associations between the results of the performed semantic and syntactic analyses are examined. According to the results of the field study, it is observed that the perception of stress of people living around the gated communities increases in proportion to the compound's syntactic values. It is understood that gated compounds in which there are homogeneous groups forming a fragmented view of the urban area shaped by urban fears, causes the perception of stress on their neighbors and that this is associated with the syntactic values of their urban locations.
Keywords: Segregation; environmental stress; gated community; othering